Un caso de malformación en Pachycheles serratus (Decapoda: Porcellanidae) - Lira, C.; Hernández, G.; Bolaños, J. A. (Revista de Biología Tropical, 2003)
An adult male of Pachycheles serratus with a malformation on the right cheliped was found during a collection of anomuran crabs in coastal waters of the peninsula de Macanao, Margarita island, Venezuela. The specimen was found at La Carmela beach (11º04'N–64°20’W), and featured a bifurcated fixed finger on the right cheliped.